Top-Level Ontologies: why do we need it and how to use it (Advances in Knowledge Representation, 2021)
Ontologies are knowledge representation artifacts that, when formals, allow unambiguous representation and interpretable by both humans and computational machines. Depending on the representation scope and the details level against the domain of knowledge, ontologies are classified into domain ontologies, reference ontologies and top-level ontologies. The first two types of ontologies cover representations of some specific domain of knowledge, but with different levels of detail. Top-level ontologies are domain-neutral ontologies that describe general concepts common across all domains. However, why do we need top-level ontologies, what are the role of these ontologies and how to use them in the design of domain or reference ontologies is not always clear. Hence, this work describes the role of top-level ontologies as representational artifacts and their contribution to the reference and domain ontologies building. Additionally, it is presented how to use them in the process of building domain or reference ontologies.